Tellurometer Operations in Topographic Mapping - Speert, Julius L. (The International Hydrographic Review, 2018)
The U.S. Geological Survey uses the Tellurometer principally to in crease the speed and reduce the costs of control surveys for topographic mapping. Increased accuracy is a welcome byproduct. In this application, it largely replaces triangulation and transit-and-tape traverse. Most of our Tellurometer work consists of traverse, with angles measured by a onesecond optical theodolite. Second-order accuracies are obtained at lower costs than for previous third-order work. All traverses are tied to the basic geodetic net. Where geodetic azimuth ties are not readily available, azimuths are obtained from Polaris observations. Our basic traverse operations are supplemented, where appropriate, by a small amount of trilateration, numerous side shots or radial measurements from strategically located control stations, and triangulation intersections of conspicuous points. The Tellurometer is also used effectively for testing the accuracy of finished maps. This report presents some statistical data on quantities, accuracies, and costs, developed during about one year of operations of four field parties. Data-reduction problems included development of a visual aid for interpreting Tellurometer coarse readings and a plastic computer for obtaining the semivelocity of the radio wave in the atmosphere as a function of wet- and dry-bulb temperatures and barometric altitudes. Vertical-angle measurements are used to reduce Tellurometer distances to horizontal and to sea level, and to compute elevations. The resulting geographic positions and elevations are adjusted by simple proration or by least squares, as appropriate.